2019
DOI: 10.3329/jbau.v17i3.43208
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the most effective plant growth-promoting bacteria from oil palm (Elaeis guineensis Jacq) roots

Abstract: A total of 30 bacterial isolates were isolated from soil, rhizoplane, and internal tissue of oil palm roots. The isolates were qualitatively tested for their potential to fix N2, solubilize inorganic P and K, and produce phytohormone indole-3-acetic acid. Of the 30 isolates, six isolates were able to exhibit multiple beneficial traits. All six isolates were then identified based on fatty acid methyl esters profile as Escherichia coli strain EX2, Serratia sp. strain EN1, Pantoea ananatis strain EN3, Bacillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Secara umum, degradasi kesehatan tanah pada lahan perkebunan dipengaruhi oleh beberapa bentuk kerusakan diantaranya teknik pertanian yang tidak sesuai, pembasmian gulma dengan herbisida secara berlebihan, berkurangnya stok bahan organik, dan meningkatnya erosi. Selain itu, penggunaan pupuk kimia yang tidak seimbang juga dapat menyebabkan degradasi kesehatan tanah dan menimbulkan efek egative terhadap lingkungan seperti keasaman tanah dan pencemaran air tanah (Zakry et al, 2019). Penggunaan produk pupuk tertentu juga dapat menyebabkan penambahan logam berat pada tanaman dan tanah (Gall et al, 2015 ).…”
Section: Pendahuluanunclassified
“…Secara umum, degradasi kesehatan tanah pada lahan perkebunan dipengaruhi oleh beberapa bentuk kerusakan diantaranya teknik pertanian yang tidak sesuai, pembasmian gulma dengan herbisida secara berlebihan, berkurangnya stok bahan organik, dan meningkatnya erosi. Selain itu, penggunaan pupuk kimia yang tidak seimbang juga dapat menyebabkan degradasi kesehatan tanah dan menimbulkan efek egative terhadap lingkungan seperti keasaman tanah dan pencemaran air tanah (Zakry et al, 2019). Penggunaan produk pupuk tertentu juga dapat menyebabkan penambahan logam berat pada tanaman dan tanah (Gall et al, 2015 ).…”
Section: Pendahuluanunclassified
“…Several microorganisms found in the rhizosphere could increase the growth and nutrient uptake of oil palm, including the use of N-fixing bacteria (Amir et al 2001, Amir et al 2005) such as Acetobacter diazotrophicus (Om et al 2009) and Bacillus sphaericus (Zakry et al 2012), and the phyla of Acidobacteria, Actinobacteria, Bacteroidates, Chloroflexi, Firmicutes, Gemmatimonadates, Nitrospirae, Proteobacteria and Thermotagae (Schneider et al 2015). Furthermore, Zakry et al (2019) reported that 7 of 30 PGPR isolates from oil palm roots (RHI1, RHI3, RHI7, EX3, EX9, EN5 and EN9) could function as N fixers. Khairani et al (2019) also reported that three genera of rhizosphere bacteria (Bacillus, Arthrobacter and Pseudomonas) were found in oil palm aged 14 years.…”
Section: Palavras-chavementioning
confidence: 99%